Electrochemically derived functionalized graphene for bulk production of hydrogen peroxide - Yeddala, Munaiah; Thakur, Pallavi; A, Anugraha; Narayanan, Tharangattu N. (Beilstein Journal of Nanotechnology, 2020)
On-site peroxide generation via electrochemical reduction is gaining tremendous attention due to its importance in many fields, including water treatment technologies. Oxidized graphitic carbon-based materials have been recently proposed as an alternative to metal-based catalysts in the electrochemical oxygen reduction reaction (ORR), and in this work we unravel the role of C=O groups in graphene towards sustainable peroxide formation. We demonstrate a versatile single-step electrochemical exfoliation of graphite to graphene with a controllable degree of oxygen functionalities and thickness, leading to the formation of large quantities of functionalized graphene with tunable rate parameters, such as the rate constant and exchange current density. Higher oxygen-containing exfoliated graphene is known to undergo a two-electron reduction path in ORR having an efficiency of about 80 ± 2% even at high overpotential. Bulk production of H2O2 via electrolysis was also demonstrated at low potential (0.358 mV vs RHE), yielding ≈34 mg/L peroxide with highly functionalized (≈23 atom %) graphene and ≈16 g/L with low functionalized (≈13 atom %) graphene, which is on par with the peroxide production using state-of-the-art precious-metal-based catalysts. Hence this method opens a new scheme for the single-step large-scale production of functionalized carbon-based catalysts (yield ≈45% by weight) that have varying functionalities and can deliver peroxide via the electrochemical ORR process.
Keywords: electrochemical oxygen reduction; functionalized carbon; functionalized graphene; H2O2 production; water treatment

(untitled) - Pesterfield, L. (J. Chem. Educ., 2009)

(untitled) - Fukuzumi, S.; Yamada, Y.; Karlin, K. D. (Electrochim. Acta, 2012)

(untitled) - Kim, H. W.; Ross, M. B.; Kornienko, N.; Zhang, L.; Guo, J.; Yang, P.; McCloskey, B. D. (Nat. Catal., 2018)

(untitled) - Campos-Martin, J. M.; Blanco-Brieva, G.; Fierro, J. L. G. (Angew. Chem., Int. Ed., 2006)

(untitled) - Iwahama, T.; Sakaguchi, S.; Ishii, Y. (Org. Process Res. Dev., 2000)

(untitled) - Zhang, J.; Chang, X.; Luo, Z.; Wang, T.; Gong, J. (Chem. Commun., 2018)

Electrochemical Water and Wastewater Treatment - Oturan, N.; Oturan, M. A. (Electro-Fenton Process: Background, New Developments, and Applications, 2018)

(untitled) - Rabaey, K.; Rozendal, R. A. (Nat. Rev. Microbiol., 2010)

(untitled) - Yang, S.; Verdaguer-Casadevall, A.; Arnarson, L.; Silvioli, L.; Čolić, V.; Frydendal, R.; Rossmeisl, J.; Chorkendorff, I.; Stephens, I. E. L. (ACS Catal., 2018)

(untitled) - Viswanathan, V.; Hansen, H. A.; Nørskov, J. K. (J. Phys. Chem. Lett., 2015)

(untitled) - Feng, Y.; Yang, L.; Liu, J.; Logan, B. E. (Environ. Sci.: Water Res. Technol., 2016)

(untitled) - Brillas, E.; Mur, E.; Sauleda, R.; Sànchez, L.; Peral, J.; Domènech, X.; Casado, J. (Appl. Catal., B, 1998)

(untitled) - Matsue, T.; Fujihira, M.; Osa, T. (J. Electrochem. Soc., 1981)

(untitled) - Brillas, E.; Sauleda, R.; Casado, J. (J. Electrochem. Soc., 1999)

(untitled) - Clerici, M. G.; Ingallina, P. (Catal. Today, 1998)

(untitled) - Ranganathan, S.; Sieber, V. (Catalysts, 2018)

(untitled) - Hâncu, D.; Beckman, E. J. (Green Chem., 2001)

(untitled) - Otsuka, K.; Yamanaka, I. (Electrochim. Acta, 1990)

(untitled) - Jiang, Y.; Ni, P.; Chen, C.; Lu, Y.; Yang, P.; Kong, B.; Fisher, A.; Wang, X. (Adv. Energy Mater., 2018)

(untitled) - Yeddala, M.; Gorle, D. B.; Anbu kulandainathan, M.; Ragupathy, P.; Pillai, V. K. (J. Colloid Interface Sci., 2019)

(untitled) - Rastogi, P. K.; Sahoo, K. R.; Thakur, P.; Sharma, R.; Bawari, S.; Podila, R.; Narayanan, T. N. (Phys. Chem. Chem. Phys., 2019)

(untitled) - Munaiah, Y.; Boopathi, S.; Senthil Kumar, S.; Ragupathy, P. (Mater. Lett., 2019)

(untitled) - Park, J.; Nabae, Y.; Hayakawa, T.; Kakimoto, M.-a. (ACS Catal., 2014)

(untitled) - Yamanaka, I.; Ichihashi, R.; Iwasaki, T.; Nishimura, N.; Murayama, T.; Ueda, W.; Takenaka, S. (Electrochim. Acta, 2013)

(untitled) - Shi, X.; Siahrostami, S.; Li, G.-L.; Zhang, Y.; Chakthranont, P.; Studt, F.; Jaramillo, T. F.; Zheng, X.; Nørskov, J. K. (Nat. Commun., 2017)

(untitled) - Campos, M.; Siriwatcharapiboon, W.; Potter, R. J.; Horswell, S. L. (Catal. Today, 2013)

(untitled) - Yamanaka, I.; Onizawa, T.; Suzuki, H.; Hanaizumi, N.; Nishimura, N.; Takenaka, S. (J. Phys. Chem. C, 2012)

(untitled) - Chen, S.; Chen, Z.; Siahrostami, S.; Kim, T. R.; Nordlund, D.; Sokaras, D.; Nowak, S.; To, J. W. F.; Higgins, D.; Sinclair, R.; Nørskov, J. K.; Jaramillo, T. F.; et al. (ACS Sustainable Chem. Eng., 2018)

(untitled) - Melchionna, M.; Fornasiero, P.; Prato, M. (Adv. Mater. (Weinheim, Ger.), 2019)

(untitled) - Pal, S.; Narayanaru, S.; Kundu, B.; Sahoo, M.; Bawari, S.; Rao, D. K.; Nayak, S. K.; Pal, A. J.; Narayanan, T. N. (J. Phys. Chem. C, 2018)

(untitled) - Sun, T.; Zhang, G.; Xu, D.; Lian, X.; Li, H.; Chen, W.; Su, C. (Mater. Today Energy, 2019)

(untitled) - Munaiah, Y.; Dheenadayalan, S.; Ragupathy, P.; Pillai, V. K. (ECS J. Solid State Sci. Technol., 2013)

(untitled) - Munaiah, Y.; Suresh, S.; Dheenadayalan, S.; Pillai, V. K.; Ragupathy, P. (J. Phys. Chem. C, 2014)

(untitled) - Vineesh, T. V.; Nazrulla, M. A.; Krishnamoorthy, S.; Narayanan, T. N.; Alwarappan, S. (Appl. Mater. Today, 2015)

(untitled) - Vineesh, T. V.; Kumar, M. P.; Takahashi, C.; Kalita, G.; Alwarappan, S.; Pattanayak, D. K.; Narayanan, T. N. (Adv. Energy Mater., 2015)

(untitled) - Kumar, M. P.; Raju, M. M.; Arunchander, A.; Selvaraj, S.; Kalita, G.; Narayanan, T. N.; Sahu, A. K.; Pattanayak, D. K. (J. Electrochem. Soc., 2016)

(untitled) - Lu, Z.; Chen, G.; Siahrostami, S.; Chen, Z.; Liu, K.; Xie, J.; Liao, L.; Wu, T.; Lin, D.; Liu, Y.; Jaramillo, T. F.; Nørskov, J. K.; et al. (Nat. Catal., 2018)

(untitled) - Kong, X.-K.; Chen, C.-L.; Chen, Q.-W. (Chem. Soc. Rev., 2014)

(untitled) - Wu, J.; Ma, L.; Yadav, R. M.; Yang, Y.; Zhang, X.; Vajtai, R.; Lou, J.; Ajayan, P. M. (ACS Appl. Mater. Interfaces, 2015)

(untitled) - Zheng, B.; Wang, J.; Wang, F.-B.; Xia, X.-H. (Electrochem. Commun., 2013)

(untitled) - Boopathi, S.; Narayanan, T. N.; Senthil Kumar, S. (Nanoscale, 2014)

(untitled) - Munaiah, Y.; Ragupathy, P.; Pillai, V. K. (J. Electrochem. Soc., 2016)

(untitled) - Yeddala, M.; Narayanan, T. N.; Pitchai, R.; Pillai, V. K. (ChemistrySelect, 2019)

(untitled) - Zhong, R.-S.; Qin, Y.-H.; Niu, D.-F.; Tian, J.-W.; Zhang, X.-S.; Zhou, X.-G.; Sun, S.-G.; Yuan, W.-K. (J. Power Sources, 2013)

(untitled) - Liu, A.; Li, W.; Jin, H.; Yu, X.; Bu, Y.; He, Y.; Huang, H.; Wang, S.; Wang, J. (Electrochim. Acta, 2015)

(untitled) - Kakaei, K.; Balavandi, A. (J. Colloid Interface Sci., 2017)

(untitled) - Qiao, X.; Liao, S.; Wang, G.; Zheng, R.; Song, H.; Li, X. (Carbon, 2016)

(untitled) - Zhao, J.; Cabrera, C. R.; Xia, Z.; Chen, Z. (Carbon, 2016)

(untitled) - Zhao, K.; Su, Y.; Quan, X.; Liu, Y.; Chen, S.; Yu, H. (J. Catal., 2018)

(untitled) - Sun, X.; Zhang, Y.; Song, P.; Pan, J.; Zhuang, L.; Xu, W.; Xing, W. (ACS Catal., 2013)

(untitled) - Deng, W.; Fang, Q.; Zhou, X.; Cao, H.; Liu, Z. (RSC Adv., 2016)

(untitled) - Zhang, H.-J.; Li, H.; Li, X.; Zhao, B.; Yang, J. (Int. J. Hydrogen Energy, 2014)

(untitled) - Tarasevich, M. R.; Bogdanovskaya, V. A.; Zagudaeva, N. M. (J. Electroanal. Chem. Interfacial Electrochem., 1987)

(untitled) - Yi, Y.; Weinberg, G.; Prenzel, M.; Greiner, M.; Heumann, S.; Becker, S.; Schlögl, R. (Catal. Today, 2017)

(untitled) - Panomsuwan, G.; Saito, N.; Ishizaki, T. (J. Mater. Chem. A, 2015)

Electrochemical methods: fundamentals and applications - Bard, A. J.; Faulkner, L. R.; Leddy, J.; Zoski, C. G. (Wiley, 1980)

(untitled) - Blizanac, B. B.; Ross, P. N.; Marković, N. M. (J. Phys. Chem. B, 2006)

(untitled) - Min, X.; Chen, Y.; Kanan, M. W. (Phys. Chem. Chem. Phys., 2014)

(untitled) - Park, S.; An, J.; Jung, I.; Piner, R. D.; An, S. J.; Li, X.; Velamakanni, A.; Ruoff, R. S. (Nano Lett., 2009)

(untitled) - Ganguly, A.; Sharma, S.; Papakonstantinou, P.; Hamilton, J. (J. Phys. Chem. C, 2011)

(untitled) - Greenhaus, H. L.; Feibush, A. M.; Gordon, L. (Anal. Chem. (Washington, DC, U. S.), 1957)